On the Rise of Bansada Agri-Eco Adventure Park in Bagumbayan, Sultan Kudarat: Voices of the Tboli Tribe - Sombero, Analyn G.; Lemana II, Henry E. (CV. Literasi Indonesia, 2024)
This descriptive-qualitative study delves into the multifaceted perceptions of the Tboli indigenous community regarding the establishment of the Bansada Agri-Eco Adventure Park in Titulok, Bangumbayan, Sultan Kudarat. Through in-depth interviews and thematic analysis, the research elucidates the diverse viewpoints encapsulating cultural significance, land contribution, economic prospects, environmental concerns, and community interactions. Ten purposively selected participants voiced a profound pride in showcasing their cultural heritage at the park, seeing it as a platform to preserve traditions and educate visitors about their ancestral practices. Their contributions to ancestral land were deeply intertwined with a sense of responsibility and cultural legacy. Economic empowerment emerged prominently, reflecting transformative shifts in livelihoods and economic prospects for the community, while environmental concerns underscored the delicate balance between development and conservation. Moreover, community interactions highlighted the pivotal role of the Tboli's engagement in decision-making processes, cultural integration within park initiatives, and their emphasis on sustainable development practices. Despite these insights, limitations in sample size, long-term impact assessment, and contextual generalizability were identified. This study offers valuable insights into the complex interplay between indigenous perceptions and local development initiatives, underscoring the need for culturally sensitive, inclusive, and sustainable approaches in such endeavors.